Neuroplasticity and activity-based rehabilitation of a patient with post-surgical chronic Pott’s spine: a case report - Raveena Kini; Prachita Walankar; Aman Minocha; Vrushali Panhale (Bulletin of Faculty of Physical Therapy)
Abstract Background India has a widespread prevalence of Pott’s disease, with an increased affection seen in young males. The common complications associated with it are spinal deformity and sensory-motor deficits in the limbs, which are based on the level of spinal affection. Case presentation We present a case of a 17-year-old male, with a history of Pott’s spine for 14 years. He has reported with anterior wedge compression and resorption of T7, T8, and T9 vertebral bodies along with Gibbus spine deformity and subsequent spinal cord compression. He underwent posterior decompression and spinal fixation with rods and pedicular screws and was referred to physiotherapy post-operatively. There is limited evidence about the emerging benefits of neuroplasticity in sequentially progressed sensorimotor skill retraining and activity-based learning as a part of rehabilitation. The patient underwent sequentially progressed mobility, balance, strength training, and activity-based relearning, which positively impacted the patient's recovery and improved quality of life. Conclusion Neuroplasticity and activity-based learning assisted in improving the functional status and quality of life in a patient surgically managed with decompression and spinal fusion post-Potts spine.